SOCIAL NETWORK SECURITY RESEARCH TRENDS: BIBLIOMETRIC ANALYSIS 2013 TO 2023 - Muchtarom, Keysha Husna; Winoto, Yunus; Rachmawati, Tine Silvana (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This research discusses the development of trends regarding social network security research. Through the bibliometric analysis method by analyzing data found in the Scopus and Dimensions databases. Trend analysis of social network security research using the Scopus and Dimensions databases provides valuable insights. The findings show consistent interest and significant growth in this research. The research focus covers various aspects of social network security, reflecting the complexity of the topic. Collaboration between researchers also proved important, with a high level of collaboration and significant international collaboration. The contributions of key researchers such as Zhang Z, Abraham A, Choo KKR, Li X, and Akhramovich V made a significant impact in this field. Frequently occurring keywords, such as “social networking (online)” and “network security,” illustrate the research focus on security aspects in the context of online social networks. The findings provide guidance for researchers to understand future trends and directions of social network security research. Overall, this analysis provides important insights into the evolution and characteristics of social network security research. These findings can be used as a basis for further research, knowledge development, and guidance for practitioners in the field of social network security.